Arbeitsmarktreform und Beschäftigung über die ökonomietheoretischen Grundlagen der Vorschläge der Hartz-Kommission (PROKLA. Journal of Critical Social Science, 2002)
The Hartz-Commission recommends the reduction of unemployment by increasing the efficiency of the labour bureau, increasing the number of low-wage jobs and subsidising firms which employ unemployed. In addition benefits especially for long-term unemployed should be cut. The hope to cut unemployment by these measures by two million until 2005 is far to optimistic. The theoretical basis of the Hartz-proposals are weak. It is not seen that changes in the structure of wages or changes in distribution generally modifY the structure of relative prices and the technology. Lower wages in these case may not lead to higher employment. The Hartz-proposals completely neglect macroeconomic dimensions of economic policy and completely concentrates on labour market flexibility and higher efficiency of the labour bureau.